Validation of the Kazakh version of the Brief Index of Affective Job Satisfaction in medical universities faculty staff sample - Assem Uristemova; Ayan Myssayev; Serik Meirmanov; Lyudmila Migina; Laura Pak; Assel Baibussinova (National Scientific Medical Center, 2023)
Aim: The present study aimed to perform validation and assessment of psychometric indicators of the Kazakh version of the Brief Index of Affective Job Satisfaction on the academic faculty staff. Material and methods: The translation of the Brief Index of Affective Job Satisfaction was performed following the World Health Organization guidelines on the translation and adaptation of research instruments. 715 medical educators of Kazakhstani medical universities represented the study population. Preliminary statistical analysis included Cronbach's alpha calculation. The psychometric properties of the instrument were examined using exploratory and confirmatory factor analysis. Results: Cronbach's alpha obtained 0.83. The Kaiser-Meyer-Olkin index reached 0.830, which indicated meritorious sample adequacy. CFA identified good factorial validity of the scale: all model fit indices exceeded the threshold values. The inter-item correlation index varied between r=0.616 and r=0.716, designating an acceptable correlation between variables. The total job satisfaction level was moderate (3.15±0.78). Women reported lower rates of job satisfaction, although the difference was not statistically significant (p<0.284). Conclusion: Our findings provide support to the psychometric properties of the Kazakh version of the BIAJS as an instrument for the assessment of job satisfaction. The major advantages of the BIAJS are that it is optimally brief, highly affective, and has good internal validity.